2014
DOI: 10.1055/s-0034-1376264
|View full text |Cite
|
Sign up to set email alerts
|

Medical Therapy for Pediatric Vascular Anomalies

Abstract: Vascular anomalies (VAs) comprise a large variety of individual diagnoses that in different phases of treatment require a diverse number of medical specialists to provide optimal care. Medical therapies include agents usually associated with cancer chemotherapy, such as vincristine, as well more immunomodulatory types of drugs, such as glucocorticoids and sirolimus. These immunomodulating drugs are being successfully applied in cases that are typically categorized as vascular tumors, including kaposiform heman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Its mechanism of action is via pathway inhibition of the mammalian target of rapamycin (mTOR), a serine/threonine kinase regulated by phosphoinositide-3-kinase (PI3K) [ 5 ]. It has been used successfully in the management of several vascular anomalies such as kaposiform hemangioendothelioma, tufted angioma, and lymphatic malformations [ 1 ]. The first case report describing response of BRBNS to sirolimus was published in 2012 by Yussekkaya et al [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its mechanism of action is via pathway inhibition of the mammalian target of rapamycin (mTOR), a serine/threonine kinase regulated by phosphoinositide-3-kinase (PI3K) [ 5 ]. It has been used successfully in the management of several vascular anomalies such as kaposiform hemangioendothelioma, tufted angioma, and lymphatic malformations [ 1 ]. The first case report describing response of BRBNS to sirolimus was published in 2012 by Yussekkaya et al [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular anomalies can be divided into two broad categories, according to the International Society for the Study of Vascular Anomalies (ISSVA) system: vascular malformations and vascular neoplasms [ 1 ]. Vascular malformations include slow-flow malformations (with venous, capillary and/or lymphatic components) and fast-flow malformations (with arterial components); while vascular neoplasms undergo mitosis and include such lesions as infantile hemangioma, congenital hemangioma, kaposiform hemangioendothelioma, tufted angioma, hemangiopericytoma, and angiosarcoma [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, sirolimus has been demonstrated to be an efficacious and safe treatment for patients with complicated vascular anomalies, included cystic lymphangiomas and diffuse lymphangiomatosis that were refractory to other therapies. [ 3 , 22 , 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…As reported in the recent literature, sirolimus has been demonstrated to be effective in the treatment of vascular anomalies, in particular in LMs and diffuse lymphangiomatosis. [ 3 , 22 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…This patient had significant response to sirolimus treatment and rapid improvement in platelet count and fibrinogen level after failure of all standard treatment algorithms 14 . In the last few years, multiple studies, including case reports and retrospective case series, have been reported using sirolimus for treatment of different vascular anomalies with positive results 4, 12, 15, 16, 17, 18, 19, 20, 21, 22. A 2011 study on 6 patients found that sirolimus is a reasonable treatment for children and young adults with complicated vascular anomalies, even when they have proven refractory to several other treatments 23 .…”
Section: Discussionmentioning
confidence: 90%